Comparative Study of the Pharmacological Properties and Biological Effects of Polygonum aviculare L. herba Extract-Entrapped Liposomes versus Quercetin-Entrapped Liposomes on Doxorubicin-Induced Toxicity on HUVECs - Mariana Mureşan; Diana Olteanu; Gabriela Adriana Filip; Simona Clichici; Ioana Baldea; Tunde Jurca; Annamaria Pallag; Eleonora Marian; Adina Frum; Felicia Gabriela Gligor; Paula Svera; Bogdan Stancu; et al. (MDPI AG, 2021)
This study aimed to evaluate the comparative biological effects of Polygonum aviculare L. herba (PAH) extract and quercetin-entrapped liposomes on doxorubicin (Doxo)-induced toxicity in HUVECs. HUVECs were treated with two formulations of liposomes loaded with PAH extract (L5 and L6) and two formulations of liposomes loaded with quercetin (L3 prepared with phosphatidylcholine and L4 prepared with phosphatidylserine). The results obtained with atomic force microscopy, zeta potential and entrapment liposome efficiency confirmed the interactions of the liposomes with PAH or free quercetin and a controlled release of flavonoids entrapped in all the liposomes. Doxo decreased the cell viability and induced oxidative stress, inflammation, DNA lesions and apoptosis in parallel with the activation of Nrf2 and NF-kB. Free quercetin, L3 and L4 inhibited the oxidative stress and inflammation and reduced apoptosis, particularly L3. Additionally, these compounds diminished the Nrf2 and NF-kB expressions and DNA lesions, principally L4. PAH extract, L5 and L6 exerted antioxidant and anti-inflammatory activities, reduced γH2AX formation and inhibited extrinsic apoptosis and transcription factors activation but to a lesser extent. The loading of quercetin in liposomes increased the cell viability and exerted better endothelial protection compared to free quercetin, especially L3. The liposomes with PAH extract had moderate efficiency, mainly due to the antioxidant and anti-inflammatory effects and the inhibition of extrinsic apoptosis.